Comparison of adrenaline injection and bipolar electrocoagulation for the arrest of peptic ulcer bleeding. Issue 5 (1st May 1999) - Lin, H-J; Tseng, G-Y; Perng, C-L; Lee, F-Y; Chang, F-Y; Lee, S-D
Abstract : BACKGROUND: Peptic ulcers with active bleeding or a non-bleeding visible vessel require aggressive endoscopic treatment. AIMS: To determine whether endoscopic adrenaline injection alone or contact probe therapy following injection is a suitable treatment for peptic ulcer bleeding. METHODS: A total of 96 patients with active bleeding or non-bleeding visible vessels received adrenaline alone, bipolar electrocoagulation alone, or combined treatment (n=32 in each group). RESULTS: Initial haemostasis was not achieved in one patient in the adrenaline group, two in the gold probe group, and two in the injection gold probe group (p>0.1). Rebleeding episodes were fewer in the injection gold probe group (2/30, 6.7%) than in the gold probe group (9/30, 30%, p=0.04) and in the adrenaline group (11/31, 35.5%, p=0.01). Treatment failure (other therapy required) was rarer in the injection gold probe group (4/32, 12.5%) than in the adrenaline group (12/32, 37.5%, p=0.04). The volume of blood transfused after entry of the study was less in the injection gold probe group (mean 491 ml) than in the adrenaline group (1548 ml, p<0.0001) and the gold probe group (1105 ml, p<0.01). Duration of hospital stay, numbers of patients requiring urgent surgery, and death rate were not statistically different among the three groups. CONCLUSIONS: For patients with peptic ulcer bleeding, combined adrenaline injection and gold probe treatment offers an advantage in preventing rebleeding and decreasing the need for blood transfusion.